Image-based Analysis for Characterization of Chicken Nugget Quality - Chumpol Yuangyai; Piyaphorn Matvises; Udom Janjarassuk (Institute of Research and Community Outreach - Petra Christian University, 2013)
Appearance, colors and adhesion characteristics of chicken nugget are important to customer satisfaction and buying decision. These characteristics are generally inspected by hu-man, thus, the inspectors might incorrectly judge. In addition, the results are not quantitatively recorded for further analysis and improvement. Therefore, this study focuses on constructing a measurement instrument for detecting the qualities of chicken nugget, then gage repeatability and reproducibility (GR&R) study is used to ensure that the instrument is capable of dis-tinguishing nugget differences. Since, there are eleven characteristics of chicken nugget are analyzed. The principal component analysis is applied to reduce the number of characteristics from eleven dimensions to only four dimensions. The experiments and data analysis show that the dimension reduction is useful for rapidly detect the abnormality of nuggets and finally help practitioners to improve the process.